Spectrophotometric determination of caffeine in tea and energy drinks - Marković, Marijana (Medicinski podmladak, 2020)
Introduction: Caffeine is a natural alkaloid, isolated from more than 60 plant species. Over 80% of the world's population consumes caffeine on daily base through the consumption of coffee, tea, chocolates and, more recently, energy drinks. As a pharmacologically potent substance caffeine is an ingredient of many medicaments available on the pharmaceutical market of Republic of Serbia without a doctor's prescription. Besides that, caffeine acts as a psychoactive stimulant substance, a mild diuretic, and indicates an interaction with some medicaments due to the induction of CYP1 and CYP2 isoenzymes. Keeping in mind all of the above, it is necessary to take into account the daily caffeine intake, as well as control its content in energy drinks.Aim: The aim of this study was spectrophotometric determination of caffeine content in energy drinks and tea, available in markets of the Republic of Serbia.Material and methods: Caffeine was determinated by UV/VIS spectrophotometry in nine types of energy drinks and eight samples of black and green tea.Results: The results showed that caffeine content in energy drink samples ranged 26,81 – 35,44 mg/mL and corresponds to declaration. The caffeine content in tea samples varies with the species (0,1127-0,2261 mg/mL for Green and 0,1385-0,2273 mg/mL for Black tea), but is also related to origin, growth conditions and tea processing.Conclusion: The data suggested that UV/VIS spectrophotometry can be used for routine determination and control of caffeine content in energy drinks and teas. It is important to note that caffeine intake through the usual daily consumption of teas and energy drinks should not have a negative impact on human health, but this alkaloid could be additionally consumed through other sources, which is especially important for certain groups of patients.Keywords: caffeine, tea, energy drinks, UV/VIS spectrophotometry